FEATURES OF DOPPLER INDICATORS OF UTERINE BLOOD FLOW IN PATIENTS WITH ADENOMYOSIS - Azizova М.E.; Magalov, I.Sh. (World of Medicine and Biology, 2024)
The purpose of study was to establish the incidence, clinical and anamnestic features of patients with adenomyosis. A comprehensive clinical, laboratory and instrumental prospective examination was carried out on 224 patients aged 30 to 50 years (average age – 42.0±1.8 years) with adenomyosis. These patients constituted the main study group. Patients of the main group were divided into 2 subgroups depending on the form of adenomyosis (Group I – diffuse form – 106 women, Group II – nodular form – 118 women). The control group consisted of 84 relatively healthy women of reproductive age, with a regular ovulatory menstrual cycle and no history of gynecological diseases. The largest number of adenomyosis are registered in patients aged 36–40 years – 92 women, 41.1±3.3 %. The most common pathologies in patients with various forms of the adenomyosis were the diseases of the cervix (114 women, 50.89±3.3 %), uterine fibroids (113 women, 50.45±3.4 %) and inflammatory diseases of the pelvic organs (113 women, 50.45±3.4 %). Resistance index values in the follicular phase and luteal phase have statistically significant differences between groups of patients with adenomyosis (p